2022
DOI: 10.3390/math10142448
|View full text |Cite
|
Sign up to set email alerts
|

Visibility Adaptation in Ant Colony Optimization for Solving Traveling Salesman Problem

Abstract: Ant Colony Optimization (ACO) is a practical and well-studied bio-inspired algorithm to generate feasible solutions for combinatorial optimization problems such as the Traveling Salesman Problem (TSP). ACO is inspired by the foraging behavior of ants, where an ant selects the next city to visit according to the pheromone on the trail and the visibility heuristic (inverse of distance). ACO assigns higher heuristic desirability to the nearest city without considering the issue of returning to the initial city or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The method fully validates that SMACFA outperforms the performance of other algorithms in solving TSP. Shahadat et al [25] proposed an improved ACO-based approach called ACO with Adaptive Visibility PLOS ONE (ACOAV). This method uses a new distance metric that incorporates partial updates of individual solutions and 3-Opt local search operations.…”
Section: Development Of Ant Colony Algorithmmentioning
confidence: 99%
“…The method fully validates that SMACFA outperforms the performance of other algorithms in solving TSP. Shahadat et al [25] proposed an improved ACO-based approach called ACO with Adaptive Visibility PLOS ONE (ACOAV). This method uses a new distance metric that incorporates partial updates of individual solutions and 3-Opt local search operations.…”
Section: Development Of Ant Colony Algorithmmentioning
confidence: 99%
“…Traditional exact algorithms have prominent disadvantages in the face of this difficulty, making it difficult to effectively solve this optimization problem [4]. To overcome this difficulty, researchers have designed many meta-heuristic algorithms inspired by the laws of physical change and biological systems in nature, such as Genetic Algorithm (GA) [5], Cuckoo Search (CS) [6], Particle Swarm Optimization (PSO) [7][8][9], Bat Algorithm (BA) [2], Simulated Annealing (SA) [10], Ant Colony Optimization algorithm (ACO) [8,[11][12][13][14], Frog-Leaping Algorithm (FLA) [15], and Artificial Bee Colony (ABC) [16][17][18][19][20]. Those kinds of meta-heuristic algorithms are simple in principle, are flexible in mechanism, and easily find the approximate optimal solution in a short time.…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional ant colony algorithm, the heuristic information is obtained by the reciprocal of the distance between nodes, without considering the need to return to the starting city in the last step. Shahadat et al [30] adopted the general formula of visibility heuristic associated with the final destination city to intelligently deal with the problem of returning to the starting city. Yu et al [31] found that the traditional ant colony algorithm would fall into the local optimum when increasing the pheromone concentration factor.…”
Section: Introductionmentioning
confidence: 99%